Identification of rare variants in KCTD13 at the schizophrenia risk locus 16p11.2. (December 2016) - Degenhardt, Franziska; Heinemann, Barbara; Strohmaier, Jana; Pfohl, Marvin A.; Giegling, Ina; Hofmann, Andrea; Ludwig, Kerstin U.; Witt, Stephanie H.; Ludwig, Michael; Forstner, Andreas J.; Albus, Margot; Schwab, Sibylle G.; et al.
Abstract : Duplications in 16p11.2 are a risk factor for schizophrenia (SCZ). Using genetically modified zebrafish, Golzio and colleagues identified KCTD13 within 16p11.2 as a major driver of the neuropsychiatric phenotype observed in humans. The aims of the present study were to explore the role of KCTD13 in the development of SCZ and to provide a more complete picture of the allelic architecture at this risk locus. The exons of KCTD13 were sequenced in 576 patients. The mutations c.6G>T and c.598G>A were identified in one patient each. Both mutations were predicted to be functionally relevant and were absent from the 1000 Genomes Project data and the Exome Variant Server. The mutation c.6G>T was predicted to abolish a potential transcription factor-binding site for specifity protein 1. Altered specifity protein 1 expression has been reported in SCZ patients compared with controls. Further studies in large cohorts are warranted to determine the relevance of the two identified mutations.